Comparison of slotted and slotless PM machines for high kW/kg aerospace applications - Dave, Nisarg; Vakil, Gaurang; Xu, Zeyuan; Gerada, Chris; Zhang, He; Gerada, David (IEEE, 2020)
With the ambitious targeted emissions reduction, the aircraft industry is moving towards drastically different aircraft architectures including hybrid-electric. These in turn require electrical machines with a step change improvement in power-density (kW/kg). This paper explores the potential of slotless surface permanent magnet (PM) machines for aerospace applications and compares the predicted power density (kW/kg) of slotless machines to their slotted counterparts.